Ghrelin promotion of oocyte maturation via ERK1/2 pathway in ovis aries - Bai, R.; Zhao, P.; Cao, G.; Wen, S.; Li, Q.; Meng, Q. (Cellular and Molecular Biology, 2012)
Ghrelin has recently garnered increasing attention in biomolecular studies. Ghrelin's growth hormone secretagogue receptor type 1a (GHS-R) is a pleiotropic modulator of diverse biological functions, including energy homeostasis and reproduction. This study sought to understand the ways in which ghrelin impacts ERK1/2 and p90rsk during the ovis aries oocyte maturation process. We applied different concentrations of ghrelin and of ghrelin receptor inhibitor (D-Lys3-GHRP-6) to ovis aries oocytes and observed the effects on the ERK1/2 and p90rsk pathway. The ERK1/2 and p90rsk pathway plays an essential role in the in vitro maturation of ovis aries oocytes. This study discovered that ERK1/2 and p90 rsk pathway, during the ovis aries oocyte maturation, was associated with maturation of ovis aries oocyte in vitro.